Transformasi metode pembelajaran melalui pendampingan Active Learning bagi guru MTsN 3 Magetan - Prayitno, Baskoro Adi; Widoretno, Sri; Sugiharto, Bowo; Prabowo, Chandra Adi; Dwiastuti, Sri (Universitas Hamzanwadi, 2023)
Active Learning is an educational approach that encourages students to actively participate in the learning-teaching process, promoting deep understanding and increasing student engagement in the classroom. Facing challenges in student-centered learning, MTsN 3 Magetan implemented training and mentoring in active learning to enhance student engagement and teacher creativity. This training, attended by 44 teachers from March to October 2023, employed blended learning methods and covered aspects such as active learning theory, literacy, and numeracy. Evaluations through pre-tests and post-tests demonstrated significant improvements in teachers’ understanding and skills. The pre-test showed an average understanding of 65%, which increased to 87% in the post-test. This active learning approach encouraged students to actively engage in the learning process, enhancing their analytical and critical skills, while teachers became more effective in designing and managing actively involved learning activities. The training contributed to improved learning effectiveness at MTsN 3 Magetan by increasing student motivation and participation, as well as teacher creativity in designing interactive learning experiences.